Kutadgu Bilig's Philosophical Context - Tasdelen, Vefa (GELENEKSEL YAYINCILIK LTD STL, 2019)
Kutadgu Bilig is one of the first works of the history of Turkish culture which shows the possibilities of Turkish in a wide area. It is a work that has not only literary but also conceptual richness and intellectual connotations that will create a philosophical context. In the answer to the question of what is philosophical text, we can say rationality, posing problems, consistency, producing new concepts, discursive approach, deep and thorough thinking, having a philosophical attitude and forming context within the history of philosophy. Many of these features can be seen in Kutadgu Bilig. First of all, is there any way to make good fortune permanent for the life of the state, society and individual; what might be the contribution of reason and knowledge about that? And raises many sub questions around that basic question. There are many terms in it that constitute the conceptual structure of the work, such as good fortune, knowledge, reason, virtue, state, justice, merit, administration, happiness, language, truth, life and death, that have a specific place in the history of philosophy. It is not difficult to say that in the history of philosophy, Kutadgu Bilig forms a context before and after itself and takes place in a tradition with the subjects and concepts it dealt with, although it is not the philosophers to whom it is explicitly referred to. Philosophical ideas, including the modem era, have emerged not only in conceptual and speculative works, but also in literary works through a story. The descriptive and imaginary literary language of these works can be translated into the conceptual language of philosophy. As for Kutadgu Bilig, he had a conceptual structure around a certain problem, which he deserved to qualify as philosophical text through a story, at a philosophical and pedagogical level, sometimes in a conceptual, sometimes descriptive and imaginary language. This conceptualization emerges in a wide range from the subject of being and knowledge to the philosophical context to the question of belief and death which is also on the agenda of modern philosophy. With this feature, Kutadgu Bilig, through Plato, Aristotle, Farabi, Ibn Khaldun, Kinalizade Ali, Locke, Rousseau, Kant, Wittgenstein, Heidegger reach the present day, can be expanded if desired on a philosophical context. Kutadgu Bilig's philosophical texture, which includes political, legal, moral, educational, religious, and other existential issues necessitates its evaluation in a philosophical context. This article, which is based on the concept of philosophical context, aims to investigate the place of Kutadgu Bilig in the history of philosophy with its basic concepts and views before and after its and to provide examples on this subject. The parallelism between philosophers and philosophies can be seen as the fact that truth manifests itself in different aspects in different cultures, places and times. In this respect, they may be called comrade thoughts or twin thoughts.
Keywords: Yusuf Khass Hajib; Kutadgu Bilig; Turkish philosophy; philosophical text; philosophical context; Arts & Humanities - Other Topics